The Relationship of Normal Postpartum Mother Knowledge and Paritives to Early Mobilization at Abi Ummi DW Sarmadi Clinic Palembang - Ratna Dewi (Science Midwifery, 2020)
Early mobilization is a policy to as soon as possible guide the patient out of bed and guide her as soon as possible to walk. Postpartum infection is a morbidity and mortality for postpartum mothers, postpartum care is needed in the postpartum period because it is a critical period for mothers. It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum deaths occur within the first 24 hours postpartum. The aim was to determine the relationship between knowledge and parity of normal postpartum mothers on early mobilization at the Abi Ummi DW Sarmadi Clinic in Palembang. Analytical survey research method with a cross sectional approach. The study population was all normal postpartum mothers who were treated at Abi Ummi DW Sarmadi Clinic Palembang. The research sample was taken purposively with a total of 26 respondents. The results of the Chi Square statistical test obtained P-Value = 0.005 <∂ (0.05), which means that there is a significant relationship between the knowledge of normal postpartum mothers and early mobilization at the Abi Ummi DW Sarmadi Clinic in Palembang in 2020. And the results of the Chi Square statistical test obtained P-Value = 0.049 <∂ (0.05) which means that there is a significant relationship between the parity of postpartum mothers and early mobilization at the Abi Ummi DW Sarmadi Clinic in Palembang.